The role of parental social class, education and unemployment on child cognitive development - Llúcia González; Rosa Cortés-Sancho; Mario Murcia; Ferran Ballester; Marisa Rebagliato; Clara Liliana Rodríguez-Bernal (Elsevier, 2020)
Objective: Assessing the association between socioeconomic gradient and cognitive development among children of a Spanish birth cohort aged 5-6 years from a gender perspective. Method: Cognitive development was assessed on 525 children aged 5-6 years in the INMA-Valencia cohort, with the Global Cognitive Score (GCS) from McCarthy Scales of Children's Abilities. Information on social class, education level and employment was collected for both parents in addition to other sociodemographic factors, parental, family and child characteristics. The relationship between maternal and paternal socioeconomic gradient and cognitive development was assessed by linear regressions and comparing the variance explained by each indicator measured in the mother and father. Results: Maternal socioeconomic gradient indicators explained more variance on GCS than paternal. Maternal education and paternal social class had an important individual effect that stayed after adjusting by other parental, child and family determinants. In the multivariable analysis, maternal education, age and intelligence, paternal social class and the child's age and sex were significantly associated with cognitive development. Conclusions: Diverse socioeconomic gradient factors have an important influence on cognitive development, maternal education being the strongest determinant. Policies should be implemented to mitigate the negative effects of this gradient on child development. Resumen: Objetivo: Evaluar la asociación del gradiente socioeconómico y el desarrollo cognitivo en niños y niñas de una cohorte española a los 5-6 años de edad desde una perspectiva de género. Método: Se evaluó el desarrollo cognitivo en 525 niños/as de 5-6 años de la cohorte INMA-Valencia, mediante la Puntuación Global Cognitiva (PGC) de las Escalas McCarthy para niños y niñas. Se recogió información de ambos progenitores sobre clase social, nivel de estudios y empleo, además de otros factores sociodemográficos, características parentales, de la familia y del niño o la niña. La relación entre el gradiente socioeconómico materno y paterno y el desarrollo cognitivo se evaluó mediante modelos de regresión lineal y comparando la varianza explicada por cada uno de los indicadores medidos en la madre y en el padre. Resultados: Los indicadores de gradiente socioeconómico de la madre explicaron más varianza del índice de PGC que los del padre. La educación materna y la clase social paterna tuvieron un importante efecto individual, que se mantuvo tras ajustar por otros determinantes de los progenitores, del niño o de la niña, y del entorno familiar. En el análisis multivariante, la educación, la edad y la inteligencia maternas, la clase social paterna, y la edad y el sexo del infante se asociaron significativamente con el desarrollo cognitivo. Conclusiones: Distintos factores del gradiente socioeconómico tienen influencia en el desarrollo cognitivo, siendo la educación materna el determinante más fuerte. Deberían implementarse políticas para paliar los efectos negativos de este gradiente en el desarrollo infantil. Keywords: Cognitive development, Socio-economic gradient, Children, Parental education, Gender perspective, Palabras clave: Desarrollo cognitivo, Gradiente socioeconómico, Infancia, Educación parental, Perspectiva de género